Effect of modified atmosphere packaging on microbial growth, quality and enzymatic defence of sanitiser washed fresh coriander. (27th October 2016) - Fang, Xiangjun; Chen, Hangjun; Gao, Haiyan; Yang, Hailong; Li, Yunlong; Mao, Peicheng; Jin, Tony Z.
Summary: Fresh coriander samples were washed in an aqueous chlorine dioxide solution and stored in modified atmosphere packaging (MAP) with air (T0), 4%O2 + 3%CO2 + 93%N2 (T1); 10%O2 + 3%CO2 + 87%N2 (T2); 15%O2 + 3%CO2 + 82%N2 (T3); 20%O2 + 3%CO2 + 77%N2 (T4) at 4 °C for 14 days. After 14 days, the ascorbic acid contents in samples were 24.8 (T3), 22.4 (T4), 19.6 (T0), 18.2 (T2) and 8.8 (T1) mg/100 g; the total phenol contents were 59.9 (T3), 53.8 (T0), 50.1 (T4), 44.8 (T2) and 39.3 (T1) mg gallic acid/100 g; and the total chlorophyll contents were 1.60 (T3), 1.52 (T4), 1.05 (T2), 0.91 (T0) and 0.63 (T1) mg g −1 respectively. T3 treatment resulted in the best colour maintenance, the least bacterial growth, and the highest activities of superoxide dismutase and catalase throughout the storage period as compared to others. The data revealed that the T3 MAP condition in combination of aqueous chlorine dioxide washing significantly ( P < 0.05) maintained the quality and extended the shelf life of fresh coriander. Abstract : Fresh coriander samples were washed in an aqueous chlorine dioxide solution and stored in modified atmosphere packaging (MAP) with air (T0), 4%O2 (T1), 10%O2 (T2), 15%O2 (T3), or 20%O2 (T4) at 4°C for 14 days. Aqueous chlorine dioxide washing (10 mg/L) effectively reduced the initial microbial loads on fresh coriander and MAP (T3) significantly inhibited microbial growth and maintained the sensory and nutritional quality during the storage. The MAP conditions promoted the antioxidant enzyme activities to prevent plant storage disorder.